Inter- and Intraspecific Geographic Variation of Body Size in South American Redbelly Toads of the Genus Melanophryniscus Gallardo, 1961 (Anura: Bufonidae) - Bidau, Claudio Juan (2011)
Amphibians show strong dependence on environmental variables (water balance, temperature). However, interactions affecting geographic distribution of body size are poorly known. We present an analysis of body size within and between species of an anuran genus using a climatic approach. We studied geographic body size distribution in 23 species of South American redbelly toads (Melanophryniscus) spanning 166 latitude, 226 longitude, and 2,400 m altitude. Body size was analyzed in relation to climatic parameters including temperature, precipitation, seasonality, evapotranspiration, and water balance at interspecific, interpopulational (all populations regardless of species), and intraspecific (populations within species) levels. LogSVL was regressed against climatic principal components scores using simultaneous autoregression. Interspecifically and interpopulationally, temperature and precipitation are the main factors responsible for the observed size clines, larger body sizes being associated with decreasing maximum ambient temperature and water availability. Intraspecific results for two species suggested comparable body-size trends. That temperature affects these size clines is reinforced by the strong positive correlation of logSVL with altitude. Because anurans strongly depend on water for survival and reproduction, it is reasonable that ,besides temperature, larger body size is favored in drier environments, which is supported by the correlation between body size and coefficients of variation of annual rainfall: lower surface : volume ratios in larger species would help conserve water in unpredictable environments. Also, Melanophryniscus has reproductive peculiarities associated with ephemeral aquatic environments: explosive breeding synchronized with rainfall; eggs deposited in several clutches; and rapid tadpole development, which suggest a strong relationship between life history and water balance.